HLA polymorphisms influence the development of skin rash arising from treatment with EGF receptor inhibitors. (October 2012) - Fuerst, Daniel; Parmar, Sumit; Schumann, Christian; Rüdiger, Stefan; Boeck, Stefan; Heinemann, Volker; Kaechele, Volker; Stiebel, Kristina; Paul, Tanusree; Seufferlein, Thomas; Mytilineos, Joannis; Stingl, Julia Carolin
Aim: Development of a skin rash under treatment with EGF receptor (EGFR) inhibitors (EGFRIs) has been linked to a favorable prognosis in some studies, suggesting a possible immunological role for EGFRIs in addition to direct antagonistic downstream effects. The present study aimed to investigate whether particular HLA polymorphisms found in cancer patients treated with EGFRIs are associated with the development of skin rash and overall survival rates.Patients & methods: HLA typing was performed on 105 cancer patients and the development of skin rash was rated during the first 4 weeks of therapy with EGFRIs.Results: A significantly lower incidence of skin rash was found in patients carrying the HLA-A*02:01 or HLA-A*03:01 alleles (hazard ratio: 0.277; 95% CI: 0.121–0.634; p = 0.002 and hazard ratio: 0.292; 95% CI: 0.113–0.752; p = 0.011, respectively); however, no association with worse survival was seen.Conclusion: The chances of developing a skin rash in patients treated with EGFRIs may be lower in patients that carry the HLA-A*02:01 or HLA-A*03:01 alleles, while the antitumor efficacy of EGFRIs does not seem to be significantly impaired in these patients. Original submitted 20 April 2012; Revision submitted 9 July 2012